v: - Eva Raudah; M. Faizin; Muhammad Rizal Akbar; Muhammad Haqqi; Erwan Setyanoor (PT. Pustaka Andil Lestari, 2025)
The issue of economic sustainability and the global environmental crisis has created an urgent need for a just, sustainable, and environmentally friendly development system. The green economy has emerged as a solution, emphasizing resource efficiency, carbon emission reduction, and social equity. In this context, Islamic economic principles and Sharia-based monetary instruments can play a strategic role in supporting the transition to green development. This article aims to examine the integration of Sharia-compliant monetary instruments such as green sukuk, mudharabah, musyarakah, productive zakat, and environmental waqf in realizing economic sustainability based on Islamic green economy principles. This research uses a qualitative method with a literature study approach. The findings show that Islamic financial instruments are not only aligned with sustainability values but also capable of promoting economic stability, empowering the real sector, and enhancing equitable wealth distribution. This integration is in line with maqashid shariah and contributes significantly to achieving the Sustainable Development Goals (SDGs). However, its implementation still faces challenges, including regulatory gaps, low public literacy, and limited access to green infrastructure. Therefore, cross-sectoral collaboration is essential to strengthen policy, expand education, and foster innovation in Sharia-based financing to achieve inclusive and sustainable development..